Simion Mehedinți (1868–1962) într-un manuscris inedit din 1934 - Magdalena Stoicescu (Revista de Istorie și Teorie Literară)
This article focuses on an unpublished manuscript of Simion Mehedinţi from 1934 which can be consulted at the Romanian Academy Library. The manuscript covers the school years of Simion Mehedinţi from the Seminary attended in Roman up to Sfântul Sava High School of Bucharest.